Analysis of daily habits and nutritional attitudes of taekwondo athletes during COVID-19 pandemic - Karagun, E.; Kahveci, M. S.; Selvi, S. (Progress in Nutrition, 2021)
Study Objectives: This study aimed to investigate whether the daily habits and nutritional attitudes of taekwondo athletes working in various regions of Turkey have changed during the COVID-19 pandemic. Upon approval of the ethics committee, it was attempted to reach the entire population of athletes who actively joined tournaments as national and amateur athletes. Methods: Prepared scale forms were opened to remote access via Google Forms and the research was announced through the agency of the federation. In the study conducted based on a voluntary basis, a 2-month time was given for filling out the scale form to collect data. At the end of the 2-month period, the research was completed with a total of 189 taekwondo athletes. Information Questionnaire identifying daily habits and socio-demographic characteristics of the participants during the pandemic, and Attitude Scale for Healthy Nutrition developed by Tekkursun Demir and Cicioglu (2019) were applied. As the data obtained were normally distributed, t test and variance analysis of parametric tests that are used for independent groups were employed. The significance level was taken as 0.05. Results: As a result; it was found that variables like gender, age, income level, father's education, years of engagement in sports, being a professional or amateur athlete caused significance difference in the attitude towards information; variables like being a national athlete, contracting COVID-19, appetite, age, education, mother's education, being a professional or amateur athlete, relatives contracting COVID-19, following news and social media caused significance difference in attitude towards positive nutritional habit; and variables like relatives contracting COVID-19, growing plants, hobby, age and mother's educational background caused significance difference in the attitude towards emotion for nutrition.